2013
DOI: 10.1158/0008-5472.can-12-0366
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor YY1 Contributes to Tumor Growth by Stabilizing Hypoxia Factor HIF-1α in a p53-Independent Manner

Abstract: In response to hypoxic stress, hypoxia-inducible factor (HIF)-1a is a critical transcription factor regulating fundamental cellular processes, and its elevated expression level and activity are associated with poor outcomes in most malignancies. The transcription factor Yin Yang 1 (YY1) is an important negative regulator of the tumor suppressor factor p53. However, the role of YY1 under tumor hypoxic condition is poorly understood. Herein, we show that inhibition of YY1 reduced the accumulation of HIF-1a and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 47 publications
6
89
0
Order By: Relevance
“…YY1 can increase Snail expression by binding to its 3 0 enhancer in melanoma cells (25). It has been indicated that silencing of YY1 disrupts the hypoxia-induced HIF1a stability and significantly suppressed growth of metastatic cancer cells (26). Significantly, previous studies have established that YY1 can interplay with P300 and CBP, as well as HDAC1, 2, 3 to recruit HDACs to repress gene transcription (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…YY1 can increase Snail expression by binding to its 3 0 enhancer in melanoma cells (25). It has been indicated that silencing of YY1 disrupts the hypoxia-induced HIF1a stability and significantly suppressed growth of metastatic cancer cells (26). Significantly, previous studies have established that YY1 can interplay with P300 and CBP, as well as HDAC1, 2, 3 to recruit HDACs to repress gene transcription (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Similar trend has been observed with intravenous injection of the same cell line into the lungs of SCID mice. 25 The decrease or plateau phase could be partially attributable to the tissue attenuation of bioluminescence signal rising from the deep tissue, resulting in unproportional increase of signal with the tumor growth. As shown in Figure 3 (lower panel), day 7 and day 14 had increasing PET SUV but similar bioluminescence signal likely due to tissue attenuation in BLI on day 14.…”
Section: Discussionmentioning
confidence: 99%
“…6). Moreover, it has been shown that YY1 is a negative regulator of p53 protein, and a positive regulator of HIF1a given that its inhibition reduces the accumulation and the activity of HIF1a under hypoxic condition (184). Such an observation suggests the involvement of HDAC-induced repressor activity of YY1 in cancer metabolic switch.…”
Section: Cross-talk Between Hdacs and Metabolism In Cancermentioning
confidence: 98%